Food intolerance in rheumatoid arthritis. II. Clinical and histological aspects. Issue 3 (March 1992) - van de Laar, M A; Aalbers, M; Bruins, F G; van Dinther-Janssen, A C; van der Korst, J K; Meijer, C J
Abstract : Six patients with rheumatoid factor positive rheumatoid arthritis who had shown a marked symptomatic improvement during four weeks of hypoallergic, artificial diet were studied in greater detail. Placebo controlled rechallenges showed intolerance for specific foodstuffs in four patients. In three of these patients biopsies of both the synovial membrane and of the proximal small intestine were carried out before and during allergen free feeding. In two patients, both with raised serum IgE concentrations and specific IgE antibodies to certain foods, a marked reduction of mast cells in the synovial membrane and proximal small intestine was demonstrated. Although the number of food intolerant patients with RA remains limited and markers of allergic activity are scanty, our observations suggest an underlying immunoallergological mechanism.